2018
DOI: 10.1002/ecy.2477
|View full text |Cite
|
Sign up to set email alerts
|

Habitat‐dependent movement rate can determine the efficacy of marine protected areas

Abstract: Theoretical studies of marine protected areas (MPAs) suggest that more mobile species should exhibit reduced local effects (defined as the ratio of the density inside vs. outside of the MPA). However, empirical studies have not supported the expected negative relationship between the local effect and mobility. We propose that differential, habitat-dependent movement (i.e., a higher movement rate in the fishing grounds than in the MPA) might explain the disparity between theoretical expectations and empirical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This has been also confirmed in fish species that show high individual variability in residence and in the spatial range of their movements (Maggs et al, 2013;Andrzejaczek et al, 2020). Some authors have suggested that this may be due to a modification of the behavior of fish within protected areas, with a higher movement rate in the fishing grounds than in the MPA (Jiao et al, 2018).…”
Section: Mpas Maintain or Recover Habitat Quality And/or Quantitymentioning
confidence: 68%
“…This has been also confirmed in fish species that show high individual variability in residence and in the spatial range of their movements (Maggs et al, 2013;Andrzejaczek et al, 2020). Some authors have suggested that this may be due to a modification of the behavior of fish within protected areas, with a higher movement rate in the fishing grounds than in the MPA (Jiao et al, 2018).…”
Section: Mpas Maintain or Recover Habitat Quality And/or Quantitymentioning
confidence: 68%
“…Overall, our model has allowed us to characterize the relative impact of epidemiological, ecological, and evolutionary dynamics in a metapopulation structure to explore how each contributes to shaping the probabilities of pathogen and host persistence. Especially as disease surveillance technologies [67][68][69] , including genetic sequencing, become more easily and affordably available, we believe this eco-evo-epi framework will be critical in generating concrete hypotheses for empirical testing and allow us a much fuller understanding of how disease risks affect the natural world.…”
Section: Discussionmentioning
confidence: 99%
“…Schematic shows how estimating the extent of edge effects (i) and spill-over (ii) differs between approaches due to different representation of spatial gradients (represented by red colour gradient and arrows) across marine reserve boundaries. areas may contribute to discontinuity across reserve boundaries (Alqawasmeh & Lutscher, 2019;Jiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Januchowski‐Hartley et al, 2013), and the impact of different modelling strategies on the interpretation of spatial gradients has not been assessed. However, theoretical modelling studies have tested assumptions regarding continuous movements across reserve boundaries and proposed behavioural aversion to harvesting activity and degraded habitats in fished areas may contribute to discontinuity across reserve boundaries (Alqawasmeh & Lutscher, 2019; Jiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%